Ruthenium-Based Small-Molecule Complexes: A Promising Approach for Drug Discovery - Purohit, Priyank; Bhatt, Akanksha; Mittal, Ravi Kumar (Synlett, 2025)
The paradigm of cancer treatment has been shifting from traditional approaches to metal-based therapies; however, achieving effective and targeted treatments remains a significant challenge. The journey of metal-based drugs began with the serendipitous discovery of cisplatin, which paved the way for the development of various platinum derivatives. Additionally, other metals, such as ruthenium (Ru), nickel (Ni), zinc (Zn), and copper (Cu), have been explored for their therapeutic potential. Among these, ruthenium-based complexes stand out due to their unique redox properties, high selectivity, and remarkable chelation capabilities, making them promising candidates for cancer therapy. This Account aims to provide a comprehensive overview of the journey of ruthenium-based metal complexes, their current status, and their pharmacological and chemical classification. These pharmacophores enable the selective delivery of cytotoxic payloads to cancer cells while sparing healthy cells. Notably, the ruthenium complex IT-139 (formerly NKP-1339) has demonstrated significant promise in clinical studies for various cancer types, exhibiting a lower toxicity than platinum-based therapies. The Account also highlights other ruthenium-based complexes and their advances. It aims to provide readers with a detailed understanding of the role of ruthenium in metal-based drug development, its mechanisms of action, and its potential applications in personalized cancer treatments. This exploration underscores the potential of ruthenium complexes, both with and without active molecules, to emerge as safe and effective therapeutic candidates in clinical oncology.1 Introduction2 Importance of Ruthenium Metal and its Complexes3 Synthesis of Ruthenium Complexes4 Classification of Ruthenium Complex Antitumor Drugs Based on their Mode of Action5 Classification of Ruthenium Complex Antitumor Drugs Based on their Structure and the Oxidation State of Ruthenium6 Current Status of Drug Clinical Trials7 Status and Applications of Metals Other than Ruthenium8 Conclusion
Keywords: ruthenium complexes; metal-based pharmacophores; cancer therapy; NKP-1339; redox activity; medicinal chemistry